Genetic and morphological diversity of various corn lines for the determination of waxy corn (Zea mays var. ceratina) parents - DIMAS AGUNG PANGESTU; SURJONO HADI SUTJAHJO; ARYA WIDURA RITONGA (Society for Indonesian Biodiversity, 2023)
Abstract. Pangestu DA, Sutjahjo SH, Ritonga AW. 2023. Genetic and morphological diversity of various corn lines for the determination of waxy corn (Zea mays var. ceratina) parents. Biodiversitas 24: 5643-5652. Genetic diversity is the first step in plant breeding programs. Information about genetic diversity is essential for commodity development to run well, and crop improvement can be more focused. This study aimed to evaluate the genetic diversity and performance of various genotypes of waxy corn. A total of 18 genotypes of waxy corn were grown using a randomized complete block design with three replications. Analysis of variance, estimation of the genetic parameters, broad-sense heritability, genotypic and phenotypic coefficient of variances, and cluster analysis were carried out in this study. The results showed differences in qualitative and quantitative characters between the genotypes of the tested waxy corn. The characters of plant height, ear height, stem diameter, number of leaves, tassel length, ear weight, and number of seeds per row had a high heritability and genetic coefficient of variance. This result indicates that those traits have a high variability among genotypes. Cluster analysis based on qualitative and quantitative characters divided 18 genotypes of waxy corn into three main clusters with similarity 18.34%. The main characteristics that divide the 3 clusters include ear weight with husk, ear length, ear length with kernels, stem diameter, plant height, and ear height. Based on the cluster analysis results, it was suspected that the F1 hybrid resulting from crossing genotypes JPM-1-5-9 with JPS-13-6-5-5 was a hybrid that could produce the best ear character.